(untitled) (Journal of International Studies, 2023)
From the end of the year 2008 to 2021, Israel committed four wars in the Gaza Strip. These wars were known as Operation Cast Lead in 2009, Operation Pillar of Cloud in 2012, Operation Protective Edge in 2014, and Operation Guardian of the Walls in 2021. The destructive impacts on vital facilities in Gaza, including schools, universities, mosques, hospitals, and United Nations Relief centers, as well as the killings of thousands of innocent civilians by Israeli forces, are visible evidence of a serious violation of the principle of distinction, a basic principle provided under the international humanitarian law conferring protection upon the civilians during armed conflicts. The accession of Palestine to the Rome Statute of the International Criminal Court on crimes. This paper aims to analyze the position of individual criminal responsibility committed during the above-mentioned wars, regulated under the Rome Statute of the International Criminal Court and other relevant international conventions. In analyzing the data from primary and secondary sources, this paper applied doctrinal legal research and qualitative approaches. This paper concludes that the Rome Statute of the International Criminal Court associated the individual criminal responsibility for war crimes by systematically determining the extent of participation, namely: (1) commission; (2) ordering/instigating; (3) assistance; and (4) contribution to a war crime as a group crime. Thus, Israeli military leaders ought to be held liable for the commission of war crimes in accordance with Article 8 of the Rome Statute of the International Criminal Court. The pretexts of the Israeli occupation to be exempt from criminal responsibility should be rejected according to the state of legitimate defense.